The Mock Application of the Insolvency Law by the Jordanian Courts: Lessons Learnt from Indonesia - Emad Mohammad Al-Amaren; Sultan Ibrahim Aletein; Kukuh Tejomurti (Faculty of Law, Hasanuddin University, 2022)
Jordan is currently going through difficult economic conditions whose features have begun to crystallize clearly since the outbreak of crises and wars in Syria and Iraq. In addition to that, the year 2020 brought with it the unknown to further complicate the Jordanian economic situation. In order to find a comprehensive solution, the Jordanian legislator used some international references, such as the principles of effective systems of creditors’ rights and insolvency issued by the World Bank and the Legislative Guide to the Insolvency Law issued by the United Nations Commission on International Trade Law (UNCITRAL) to rescue faltering economic projects or those that are about to stumble. The study resulted in the issuance of the Jordanian Insolvency Law No. 21 of 2018. This paper aims to identify the insolvency standard of the Jordanian courts and its impact on Jordan's economy. By applying a qualitative legal approach, this paper analyses the mock application of the Insolvency Law by the Jordanian courts. It also examines the insolvency standard followed by the Jordanian courts via juridical-normative with descriptive analysis. The finding shows that applying the insolvency law in Jordan is still a theory. Jordanian courts should cautiously extend the scope of insolvency theory for the law to achieve the purpose for which it was issued. Comparing the practice in Indonesia, which has switched from the insolvency test concept to the presumption of bankruptcy, this is a lesson because, in the conditions of the COVID-19 pandemic, companies will find it challenging to request reports due to uncertain situations. According to the financial aspect, large companies are still good, but companies are reluctant to pay debts. This condition means that if the system used is a bankruptcy test, this case cannot be brought to the Commercial Court, so the court cannot force debtors who are reluctant to pay their debt obligations.